Prosedur Penegakkan Hukum Pada Masyarakat Yang Terlibat Tindak Pidana Narkotika : di Wilayah Polda Kalimantan Timur - Aristo Wanatirta; Ilham Prisgunanto (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study examines the law enforcement procedures applied to communities involved in narcotics crimes within the jurisdiction of the East Kalimantan Regional Police. The objective of this study is to analyze the application of law enforcement procedures by police officers toward individuals involved in narcotics-related offenses. This research utilized a qualitative approach using a juridical-empirical method, which examines the implementation of legal norms in actual law enforcement practices within society. Primary data were obtained through in-depth interviews with investigators from the Directorate of Narcotics Investigation of the East Kalimantan Regional Police, individuals who have experienced the narcotics law enforcement process, expert witnesses, and affected parties. The results indicate that the law enforcement procedures for narcotics crimes within the East Kalimantan Regional Police generally follow the applicable legal framework, particularly Law Number 35 of 2009 concerning Narcotics and criminal procedural law. This study concludes that effective narcotics law enforcement requires strengthening the capacity of law enforcement officers, improving inter-agency coordination, and enhancing public legal awareness to support more effective law enforcement practices.